A Review of Recent and Emerging Approaches for the Clinical Application of Cerenkov Luminescence Imaging - Mc Larney, Benedict; Skubal, Magdalena; Grimm, Jan (Frontiers in Physics, 2021)
Cerenkov luminescence (CL) is a blue-weighted emission of light produced by a vast array of clinically approved radioisotopes and LINAC accelerators. When β particles (emitted during the decay of radioisotopes) are present in a medium such as water, they are able to travel faster than the speed of light in that medium and in doing so polarize the molecules around them. Once the particle has left the local area, the polarized molecules relax and return to their baseline state releasing the additional energy as light (luminescence). This blue glow has commonly been used to determine the output of nuclear power plant cores and, in recent years, has found traction in the preclinical and clinical imaging field. This brief review will discuss the technology which has enabled the emergence of the biomedical Cerenkov imaging field, recent pre-clinical studies with potential clinical translation of Cerenkov luminescence imaging (CLI) and the current clinical implementations of the method. Finally, an outlook is given as to the direction in which the field is heading.